Pengembangan Sistem Rekomendasi Lokasi Kegiatan Dengan Metode Augmented Reality - I Gusti Agung Gede Arya Kadyanan (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2022)
The buildings owned by Udayana University are quite numerous by providing different facilities. So that in carrying out an activity, the implementer must adjust what facilities are needed in the activity. In addition, the implementers of the activity must also come and see first hand the condition of the building or room that wants to be used as the location of the activity, so that it will take a long time. There is a need for a system that can recommend the location of activities of Udayana University in accordance with the implementing needs of the activity. This study designed and built a recommendation system for the location of activities in the Udayana University using the Simple Additive Weighting (SAW) and Augmented Reality methods. The application will be used by the user to get the location that suits their needs. The results of this study, in the android application has been able to make recommendations and plotting the location of activities in the Udayana University, as well as display information in the form of 3D objects through Augmented Reality technology. Keywords: Recommendation System, Activity Location, Augmented Reality, Android, Udayana University